The ballroom dance pack - Laird, Walter
This comprehensive teaching program introduces you to the six most popular social dances: the waltz, the quickstep, the tango, the rumba, the samba, and the cha-cha. The full-color guide shows you all the steps and combinations necessary to dance complete figures around the floor, and contains special practice exercises to loosen you up and help you master the essential rhytms